Evangelische Theologie (Gütersloher Verlagshaus, 1934)
With its interdisciplinary approach and thematically arranged issues, Evangelische Theologie makes crucial contributions to the exploration of the complex field of theology. In addition to such thematic issues, open issues without special thematic commitment are specifically devoted to one of the theological disciplines. The issues of Evangelische Theologie make both the hot spots of theological discourse and the most recent developments of research within the individual theological disciplines accessible not only to pastors, students, and teachers, but also to non-experts, while at the same time exceeding the range of the mere theological disciplines. ---------- PRINT available from Gütersloher Verlagshaus:http://www.fachzeitschriften-religion.de/evangelische-theologie